Cell Volume Measurements by Optical Transmission Microscopy. Issue 1 (1st April 2015) - A. Model, Michael
Abstract: Cell volume is an important parameter in cell adaptation to anisosmotic stress, in the development of apoptosis and necrosis, and in the pathogenesis of several diseases. This unit describes a method for measuring the volume of adherent cells using a standard light microscope. A coverslip with attached cells is placed in a shallow chamber in a medium containing a strongly absorbing and cell‐impermeant dye, Acid Blue 9. When such a sample is imaged in transmitted light at a wavelength of maximum dye absorption (630 nm), the resulting contrast quantitatively reflects cell thickness. Once the thickness is known at every point, the volume can be computed as well. Technical details, interpretation of data, and possible artifacts are discussed. Measurements in absolute units require knowledge of the absorption coefficient, and a similar procedure for the measurement of absorption coefficient is described. © 2015 by John Wiley & Sons, Inc.